Design and Implementation of a Visible Light-Based Pest Stinger System - Wahab, Faisal; Maria Diamond, Ivana; Fredy Naa, Christian (Universitas Muhammadiyah Surakarta, 2025)
The agricultural yield in Indonesia has been declining, partly due to shrinking farmland. To address this issue, urban farming has been developed as a solution. However, in urban farming, there is a problem where the leaves of vegetables are infested by insect pests, causing damage to the leaves. Therefore, pest control is necessary in the farming area. One alternative for controlling insect pests is by applying high-voltage electricity to the pests, which will kill them by electric shock with a voltage of around ±1 kV. A